Marriage Guidance as an Effort to Prevent Divorce from the Perspective of Islamic Family Law: A Study at the Bandung City AMCDP (Agency for Marriage Counselling, Development, and Preservation) - Nabila Silmi Amatillah; Didi Sumadi; Harry Yuniardi (International Journal of Nusantara Islam, 2026)
This study examines the implementation of marriage guidance at the Bandung City AMCDP (Agency for Marriage Counselling, Development, and Preservation)’—known as BP4 (Badan Penasihatan, Pembinaan, dan Pelestarian Perkawinan)—as a preventive mechanism against divorce, analyzed through psychological, sociocultural, and Islamic legal perspectives. Using a qualitative case-study design, data were collected through in-depth interviews with institutional leaders, observations of counselling sessions, and documentation of program guidelines. The findings demonstrate that AMCDP employs a multilayered guidance model comprising premarital education, post-marital enrichment, conflict counselling, spiritual strengthening, and structured mediation. These practices integrate psychological intervention skills—such as communication training and emotional-regulation techniques—with Islamic ethical principles, including iṣlāḥ, muʻāsharah bi al-maʻrūf, and the preservation of marriage as mīṡāqan ghalīẓan. The institution also plays a mediational role mandated by Indonesian marriage law, particularly in pre-divorce reconciliation procedures. The study concludes that AMCDP represents a hybrid institution bridging religious norms, legal mandates, and psychosocial realities to strengthen marital resilience. This model contributes to Islamic family-law scholarship by demonstrating how classical jurisprudential principles can be operationalized into contemporary counselling practice to prevent divorce.